An Atmosphere-Breathing Refillable Biphasic Device for Cell Replacement Therapy - An, Duo (Adv Mater, 2019)
Cell replacement therapy is emerging as a promising treatment platform for many endocrine disorders and hormone deficiency diseases. The survival of cells within delivery devices is, however, often limited due to low oxygen levels in common transplantation sites. Additionally, replacing implanted devices at the end of the graft lifetime is often infeasible and, if possible, generally requires invasive surgical procedures. This report presents the design and testing of a modular transcutaneous biphasic cell delivery device which provides enhanced and unlimited oxygen supply by direct contact with the atmosphere. Critically, the cell delivery unit was demountable from the fixed components of the device, allowing for surgery-free refilling of the therapeutic cells. Mass transfer studies showed significantly improved performance of the biphasic device in comparison to subcutaneous controls. The device was also tested for islet encapsulation in an immunocompetent diabetes rodent model. Robust cell survival and diabetes correction was observed following a rat-to-mouse xenograft. Lastly, non-surgical cell refilling was demonstrated in dogs. These studies show the feasibility of this novel device for cell replacement therapies